Effectiveness of hand washing on the removal of iron oxide nanoparticles from human skin ex vivo. Issue 8 (3rd August 2017) - Lewinski, Nastassja A.; Berthet, Aurélie; Maurizi, Lionel; Eisenbeis, Antoine; Hopf, Nancy B.
ABSTRACT: In this study, the effectiveness of washing with soap and water in removing nanoparticles from exposed skin was investigated. Dry, nanoscale hematite (α-Fe2 O3 ) or maghemite (γ-Fe2 O3 ) powder, with primary particle diameters between 20–30 nm, were applied to two samples each of fresh and frozen ex vivo human skin in two independent experiments. The permeation of nanoparticles through skin, and the removal of nanoparticles after washing with soap and water were investigated. Bare iron oxide nanoparticles remained primarily on the surface of the skin, without penetrating beyond the stratum corneum. Skin exposed to iron oxide nanoparticles for 1 and 20 hr resulted in removal of 85% and 90%, respectively, of the original dose after washing. In the event of dermal exposure to chemicals, removal is essential to avoid potential local irritation or permeation across skin. Although manufactured at an industrial scale and used extensively in laboratory experiments, limited data are available on the removal of engineered nanoparticles after skin contact. Our finding raises questions about the potential consequences of nanoparticles remaining on the skin and whether alternative washing methods should be proposed. Further studies on skin decontamination beyond use of soap and water are needed to improve the understanding of the potential health consequences of dermal exposure to nanoparticles.